2010
DOI: 10.1111/j.1462-5822.2009.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-type oxygen detoxification and iron-sulfur cluster assembly in amoebal relict mitochondria

Abstract: SummaryThe assembly of vital reactive iron-sulfur (Fe-S) cofactors in eukaryotes is mediated by proteins inherited from the original mitochondrial endosymbiont. Uniquely among eukaryotes, however, Entamoeba and Mastigamoeba lack such mitochondrial-type Fe-S cluster assembly proteins and possess instead an analogous bacterial-type system acquired by lateral gene transfer. Here we demonstrate, using immunomicroscopy and biochemical methods, that beyond their predicted cytosolic distribution the bacterial-type Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 57 publications
2
67
1
Order By: Relevance
“…support previous report suggesting that NIF components function in the mitosomes in addition to the cytosol of E. histolytica (18).…”
Section: Components Of E Histolytica Nif Machinery Do Not Possess Mtsupporting
confidence: 80%
See 2 more Smart Citations
“…support previous report suggesting that NIF components function in the mitosomes in addition to the cytosol of E. histolytica (18).…”
Section: Components Of E Histolytica Nif Machinery Do Not Possess Mtsupporting
confidence: 80%
“…Therefore, the predominant cytosolic distribution of the NIF machinery should be sufficient to accommodate the cellular requirements for FeS cluster biogenesis in this organism. Surprisingly, dual localization of the NIF machinery in the cytosol and the mitosomes of E. histolytica has also been suggested, and FeS cluster biogenesis has been proposed as one of the fundamental functions of entamoebal mitosomes (18). However, following proteomic analysis of E. histolytica mitosomes has not confirmed the presence of NIF machinery (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Blastocystis SUF machinery, we sought to investigate the localization and function of its putative mitochondrial ISC system previously suggested to function within its biochemically unique anaerobic MRO (12,13). The unusual properties of the Blastocystis MRO raises questions about the localization and functionality of its ISC machinery, especially because recent studies have shown that other parasitic anaerobic protists with MROs, including the microsporidian Trachipleistophora hominis and the amoebozoan Entamoeba histolytica, may have relocated some components of their Fe/S cluster biosynthetic machinery into the cytosol (7,27). Our investigations reveal that Blastocystis possesses homologues of nearly all components of the mitochondrial ISC machinery in yeast (SI Appendix, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotes, Fe/S proteins are assembled by several different systems, including the ISC assembly and the sulfur-mobilization (SUF) machineries, which are found only in mitochondria and plastids, respectively. Two exceptions to this rule are found in Entamoeba histolytica and Mastigamoeba balamuthi, which possess nitrogen fixation-type Fe/S systems, although the subcellular localizations of these systems remain controversial (7,8). The maturation of cytosolic and nuclear Fe/S proteins in eukaryotes is typically dependent on the cytosolic iron/sulfur assembly (CIA) machinery, which is essential in yeast and is found in all eukaryotes investigated so far (9).…”
mentioning
confidence: 99%